Association of Device‐Measured Habitual Sedentary Activity and Standing Posture With Blood Pressure and Hypertension in Danish Adults: The Lolland‐Falster Health Study - Sofie Rath Mortensen; Jan Christian Brønd; Therese Lockenwitz Petersen; Randi Jepsen; Fernando Domínguez‐Navarro; Søren T. Skou; Anders Grøntved (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Limited evidence exists on the link between sedentary activity and blood pressure (BP), especially using combined thigh‐ and back‐worn accelerometry, which offers accurate posture classification. This study examined the association between device‐measured sedentary activity patterns and BP levels and hypertension and explored whether obesity explained these associations. Methods This cross‐sectional study included 3127 adults (≥18 years) from the Danish Lolland‐Falster Health Study (2017–2020). The outcome was participants' systolic BP and diastolic BP in mm Hg measured by a health care professional. Exposure was time spent on sedentary activity (duration, postures, prolonged bouts and breaks in sedentary activity) during the day assessed with thigh‐worn and back‐worn accelerometers. Multiple regression models were used to investigate if sedentary activity was associated with BP levels. Results Participants with hypertension, standardized for age and sex, were more sedentary (9.4 hours/day), had fewer sedentary breaks (54 breaks/day), and more prolonged sedentary bouts (5 bouts/day) compared with those without hypertension. Daily number of sedentary breaks between ≥50 to <65 and ≥65 was associated with lower systolic BP (−1.8 mm Hg [95% CI, −3.3 to −0.3] and −2.3 mm Hg, [95% CI, −3.8 to −0.7]) when compared with participants with daily breaks <50. Higher total daily sedentary time was associated with higher diastolic BP (0.3 mm Hg per hours/day [95% CI, 0.05–0.5]). Conclusions Higher total sedentary time and prolonged sedentary bouts were associated with higher diastolic BP, independent of lifestyle factors. Conversely, a higher number of sedentary breaks was associated with lower systolic BP, diastolic BP, and lower odds of hypertension. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT02482896.